The first study on population knowledge and attitudes regarding prevention, diagnostic methods, treatment, and recovery aspects related to Helicobacter pylori infection in Bosnia and Herzegovina - Bektas, Nejra; Besic, Larisa; Kulo Cesic, Aida; Marjanovic, Damir; Prguda-Mujic, Jasminka (Frontiers in Public Health, 2025)
The aim of this pioneering study was to examine the knowledge and attitudes regarding prevention, diagnostic methods, treatment, and recovery aspects related to Helicobacter pylori infection within the general population of Bosnia and Herzegovina (B&H). Study was conducted using the previously designed questionnaire, adapted for the B&H population. The research enrolled 1,031 participants, of whom 58.49% answered predominantly correctly to questions regarding Helicobacter pylori infectivity. Of all participants, 36.18% underwent screening, with 65.95% testing positive, and of those, 93.90% received treatment, mainly antibiotics (92.64%). Of those treated, 74.46% were re-tested and 30.23% of them had relapsed infection. Furthermore, the study identified lower infection rate in younger participants and, contraversaly, in participants with the history of long-term (lasting for more than a year) alcohol consumption, who were also shown to report symptoms' improvement post-treatment. Overall, B&H population demonstrated good knowledge toward Helicobacter pylori infection, with higher levels of knowledge in women, highly educated, or screened for H. pylori. Notably, participants expressed strong support for national Helicobacter pylori screening and thus underscored the importance of planning it in the public health initiatives in B&H. Also, due to the high relapsed infection rate, further effort needs to be directed toward education of risk groups i.e., older age groups, and community on effective measures for Helicobacter pylori prevention and treatment.